Effect of Mini-plate Fixation on Hinge Fracture and Bony Fusion in Unilateral Open-door Cervical Expansive Laminoplasty. Issue 6 (July 2016) - Chen, Hua; Liu, Hao; Zou, Li; Li, Tao; Gong, Quan; Song, Yueming; Zeng, Jiancheng; Liu, Limin; Kong, Qingquan
Abstract : Study Design: This was a retrospective study. Objective: The aim of this study was to investigate the effect of Centerpiece mini-plate fixation on the complete fracture and bony fusion of the hinge side in unilateral open-door cervical expansive laminoplasty. Summary of Background Data: Cervical laminoplasty is an effective and safe surgery for cervical canal stenosis. The Centerpiece mini-plate is an instrument used to secure the laminae and maintain the cervical canal expansion. Stability of the new laminae is largely dependent on healing of the hinge side bone fracture and the degree of bony fusion. To date, few studies have reported on the effects of mini-plate fixation on these 2 important factors. Materials and Methods: Between September 2009 and March 2011, 58 patients received unilateral open-door cervical expansive laminoplasty at the authors' hospital. The group included 47 male and 11 female patients, with a mean age of 61 (range, 35–81) years. Two hundred twenty-five laminae were fixed using the Centerpiece mini-plate (group A), whereas 62 laminae were fixed using suture suspension (group B). The rates of fracture and bony fusion of the hinge were observed using computed tomography scan and compared between the 2 groups. The complete fractures were subdivided into 4 groups based on the degree of displacement of the fractured ends: type I (no displacement), type II (mild to moderate displacement), type III (complete displacement or separation), or type IV (the hinge had collapsed into the cervical canal). Results: The number of incomplete fractures and type I to IV fractures in group A were 95, 93, 25, 8, and 4 and 29, 25, 4, 2, 2 in group B, respectively. There were no significant differences between the 2 groups in terms of complete fracture rates ( P= 0.309) and complete fracture type distribution ( P= 0.694). Group A had a significantly higher rate of bony fusion of the hinge 3 months after surgery (82% vs. 70%, P= 0.042); however, this rate was not statistically significant 6 months after surgery ( P= 0.141). For type I complete hinge fracture, group A had higher bony fusion rates, both 3 months (86% vs. 57%, P= 0.004) and 6 months (92% vs. 85%, P= 0.048) postoperatively. The rates of bony fusion were also significantly different among all complete fracture types 3 months ( P <0.001) and 6 months ( P <0.001) postoperatively. Conclusions: Centerpiece mini-plate fixation in unilateral open-door cervical expansive laminoplasty might not increase the complete fracture rate compared with suture suspension and might promote bony fusion of type I complete hinge fractures.